Steroid Receptor Coactivator (SRC) Family: Masters of Systems Biology - York, Brian (American Society for Biochemistry and Molecular Biology, 2010)
The three members of the p160 family of steroid receptor coactivators (SRC-1, SRC-2, and SRC-3) steer the functional output of numerous genetic programs and serve as pleiotropic rheostats for diverse physiological processes. Since their discovery ∼15 years ago, the extraordinary sum of examination of SRC function has shaped the foundation of our knowledge for the now 350+ coregulators that have been identified to date. In this perspective, we retrace our steps into the field of coregulators and provide a summary of selected seminal work that helped define the SRCs as masters of systems biology.